Study on seismic mitigation Performance of Long-span High-speed Railway Continuous Beam Bridge with Viscous Damper. Issue 1 (1st January 2022) - Quan, W; Yu, HM; Wen, X; Liu, ZX
Abstract: Taking the 128m long-span high-speed railway continuous beam bridge commonly used in China as the example, a reasonable finite element analysis model with seismic mitigation devices of the bridges is established, and nonlinear dynamic time history analysis is used to analyze the seismic mitigation of viscous dampers. three seismic waves with the same peak acceleration but different spectral components are selected to perform optimization analysis on the viscous damper parameters, damping index and damping coefficient. Numerical analysis results show that: (1) The viscous damper can play a very good damping effect. (2) Under the action of the El Centro wave and Tianjin wave, the damping rates of the fixed pier reached more than 81%. Under the action of Taft wave, except for the relative displacement of the fixed-pier, the damping rates of the structure reached more than 74%; The internal force of the other piers and the displacement of the top of the pier increase, but the increase is not large compared with the response value of the fixed pier, and the forces on the piers tend to be uniform and reasonable. (3) The three kinds of seismic wave have different optimization results for the mechanical parameters of the viscous damper model. When selecting the actual devices parameters, the ground motion with the corresponding spectral characteristics should be selected according to the bridge site for optimization analysis. Besides, the devices structure, size requirement and other reason should be considered comprehensively.